Postcolonial fissures and the contingent nation an antinationalist critique of Philippine historiography - Claudio, Lisandro E. (2013)
This article examines instances in Philippine historiography where nationalism, as a unitary end, has been used to elide and obscure class difference. It begins with a partial explanation of the lacunae in antinationalist thinking in the Philippines, and then proceeds to a critique of contemporary nationalist historiography. Using historians Zeus Salazar and Reynaldo Ileto as case studies, it examines how nationalist historiography can serve as means to implicitly justify localized acts of class oppression. The works of these scholars, while crucial in forwarding critiques of colonialism and neocolonialism, privilege nationalist unity over thorough examinations of disjunctures produced by class difference.
Keywords: Philippines -- Historiography; Historians -- Political and social views; Nationalism